2011
DOI: 10.3851/imp1894
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Viral Response of Once-Daily Tmc435 plus Pegylated Interferon/Ribavirin in Hepatitis C Genotype-1 Patients: A Randomized Trial

Abstract: Once-daily TMC435 with P/R showed potent, dose-dependent antiviral activity over 28 days, and had a favourable tolerability profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…A 200 mg dose was selected as this was the highest dose which was previously administered to patients infected with HCV genotype 1 in the TMC435-C201 trial [35], had previously exhibited a good safety and tolerability profile, and had also maximised the potential for antiviral activity across all genotypes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 200 mg dose was selected as this was the highest dose which was previously administered to patients infected with HCV genotype 1 in the TMC435-C201 trial [35], had previously exhibited a good safety and tolerability profile, and had also maximised the potential for antiviral activity across all genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Phase I and II trials in patients infected with HCV genotype 1 have demonstrated that TMC435 is generally well tolerated, has a pharmacokinetic profile that supports once daily (q.d.) dosing, and demonstrates potent antiviral activity and efficacy [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The main side effect of RBV is hemolytic anemia, which increases the heme load, resulting in usually mild, indirect hyperbilirubinemia that is isolated (i.e., with no other clinical symptoms indicative of liver injury) (Korenblat and Berk, 2005;McHutchison et al, 2009;Perico et al, 2009). Hyperbilirubinemia or anemia has been reported during trials of a number of other HCV protease inhibitors currently approved or in clinical development, such as telaprevir (Zeuzem et al, 2011), asunaprevir (Suzuki et al, 2013), daclatasvir (Suzuki et al, 2013), simeprevir (Manns et al, 2011b), and ABT-450 (paritaprevir; AbbVie, Chicago, IL; Poordad et al, 2013). Second-wave direct-acting antivirals, including simeprevir, sofosbuvir, and faldaprevir, demonstrate better efficacy over a shorter treatment duration and improved safety profiles, compared with earlier directacting antivirals (Asselah and Marcellin, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Isolates collected pretreatment, at the time of failure, at the end of the study, and/or at other time points during the study of HCV genotype 1-infected patients naive to HCV NS3/4A protease inhibitors who received simeprevir alone (clinical studies TMC435-C101 [13] and -C201 [14]) or who were treated with simeprevir in combination with PegIFN/RBV (clinical studies TMC-C201, -C205 [15], -C206 [16], -C208 [3], -C216 [2], and HPC3007 [4]) were selected for phenotypic analysis. In addition, 4 pretreatment isolates from 4 patients enrolled in the placebo arm of clinical study TMC435-C201 were analyzed.…”
Section: Methodsmentioning
confidence: 99%